Peer-harassment prevalence in self-reports by primary and lower secondary school students. Statistical comparisons of samples from years 2000 and 2013, investigating traditional and cyber-harassment. - Hjelmen, Kari Jeanette Langseth (UiT Norges arktiske universitet, 2015)
Comparative investigation of traditional peer-harassment and cyber-harassment prevalence, examining first year baseline sample of a longitudinal project in a North-Norwegian setting. Thesis contributes into a main study, “Trivsel i Tromsø” (“Well-being in Tromsø”), which aims to examine psychosocial and psychiatric risk factor associations with bullying and cyberbullying, using a combination of survey tools. The thesis explore one of the three survey tools. Investigation of sample administered in school setting, supplemented with survey data from previous study, thus contrasting harassment prevalence in the same five schools before and after the “mobile phone revolution” using the “My Life in School Checklist +” at two points in time, years 2000 and 2013. There is reduction between years on physical and verbal harassment, at the same time digital harassment appear with low scores. Social harassment show no significant difference between years. The cyber-harassment composite show no significant gender difference. Younger grades show less cyber-harassment than older grades. Regarding types of harassment, girls receive more cyber-harassment through social media and websites, whereas boys receive more through chat as at Skype or within games.